Priene, Türkei. Die Fundmünzen von Priene. Die Arbeiten in den Jahren 2015 bis 2017 - Eberhardt, Johannes; Weisser, Bernhard (e-Forschungsberichte des DAI, 2019)
The coin finds of Priene form one of the most important groups of numismatic material of western Asia Minor. The site of ancient Priene, which was never affected by medieval or modern settlement, provides a wealth of information on Hellenistic urbanism. At the end of the 19th century excavations unearthed over 6.100 coins which were later transferred to the Berlin Münzkabinett. Together with the coin finds from the Athenian agora those of Priene include the highest number of published pre-imperial objects. Since 1998 new archaeological field work provides additional insights and has currently added more than 1.500 new coin finds. In 2005 the Münzkabinett reinitiated its early 20th century research projects on the coin finds of Priene. The following survey contextualizes work and results of a two-year DAI post-doc scholarship (2015–2017). The most important feature of this recent period of research is the creation of an open access publication and data-base of the coin finds of Priene at ww2.smb.museum/mk_priene.